(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the specific features of the ballet-mas ten profession. The main tasks in the work with the children’s choreographic group are determined, and the main teaching methods as means of influence on the pupils and on the level of the improving of the own pedagogical s kills, are determined, too.